Democratic Representation in Japanese Defense Spending: Does Public Sentiment Really Matter? - Takao, Yasuo (Canadian Center of Science and Education, 2011)
Japan’s level of defense spending relative to the size of its economy has been anomalously low among the major industrialized countries. Much of the literature on Japan’s national security suggests that antimilitarist public sentiment constraints Japanese defense budgeting. A substantial amount of research is methodologically descriptive and the policy impact of Japanese public opinion is largely presumed but not closely tested. This study tested the relationship between Japanese public opinion and defense spending. In the process of testing, the existing measurement theory, which has accounted for cases in Western Europe and the Unites States, has been found inadequate to explain the Japanese causal link. With the introduction of alternative measurements, this study found that Japanese public opinion does uniquely constrain defense budget decisions.